PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF MULTI-DRUG RESISTANT ESCHERICHIA COLI ISOLATES FROM URINARY TRACT INFECTION (UTI) PATIENTS: Life Science-Microbiology - MEHTA, MANJULA; BHARDWAJ, SONIA; SHARMA, JYOTI (International Journal of Life Science and Pharma Research, 2012)
Background-E.coli is found to be the commonest cause of UTI. However E. coli antibiotic resistance has escalated over the past many years. Objective- To provide an update of prevalence of multidrug resistant E.coli isolates and their antibiotic susceptibility pattern with special reference to northern region of Chandigarh. Methods- This retrospective study was conducted in the Department of Microbiology, Dr Harvansh Singh Judge Institute of Dental Sciences and Hospital, Panjab University from January, 2010 to December,2011 using urine samples from outdoor patients of UTI from healthcare centre, Panjab University, Chandigarh. A total of 307 urine samples were processed for bacterial culture using standard methods. For these urinary isolates, susceptibility to various antibiotics was checked as per standard CLSI guidelines. Final resistance to various antibiotics from the urinary isolates was analysed. Results- A total of 75 urine samples (41%) showed growth of E. coli. Out of these 43 isolates (57%) were multi drug resistant. High level of resistance was seen to ciprofloxacin, amoxicillin, cotrimaxozole, norfloxacin ranging from 70-95% whereas combination drugs (piperacillin +tazobactam),(ceftazidime + clavulinic) along with amikacin, imipenem showed low level of resistance. However Nitrofuratoin was found to be highly sensitive to all urinary isolates of E.coli including multidrug resistant strains.Conclusion- E.coli was found to be the commonest cause of UTI in our study population. Multidrug resistance was high among the prevalent strains which emphasizes the judicious use of antibiotics.